A Review on Synchronous, Asynchronous, and Blended Learning on ELT in Indonesian Context - Eka Fajar Rahmani; Riyanti, Dwi; Misieng, Jecky; Sayok, Alexander K (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2024)
This study analyzes Indonesian EFL teachers' synchronous, asynchronous, and blended learning implementation during the Covid-19 pandemic. Numerous articles have been published this trend. Unfortunately, the early search only found implementation or student/teacher perspectives research. One-article works on other learning modes are preferable. Thus, using PRSIMA's Systematic Literature Review (SLR) design, the researchers chose 32 of 82 related papers from qualified publications approved by SINTA 1, 2, and 3. The study addresses six key points: implementation of the three learning modalities, urban-rural contrasts, most used platforms, students' and teachers' opinions, obstacles they face, and solutions. After COVID-19 broke out, researchers became more interested in these learning modalities, highlighting their importance. This review also analyzes how teachers used digital platforms to engage students throughout synchronous, asynchronous, and blended learning courses. Even though students and teachers faced classroom management, technological issues, platform unfamiliarity, and internet limits, they still liked the learning modes. They liked the modalities' practicality, adaptation, and flexibility, especially for English acquisition. EFL teachers, educators, researchers, and policymakers can use this review to gain a comprehensive understanding of synchronous (virtual real-time activity), asynchronous (learning at different times), and blended learning.